The effect of steering on stride pattern & velocity in long jump - Galloway, M.; Connor, K. (ISBS - Conference Proceedings Archive (Konstanz), 1999)
The purpose of this study was to identify whether visual control strategies (or steering) in the long jump run-up had an effect on the subsequent velocity, or the stride pattern, after the point of steering. Three Australian long jumpers were recorded on videotape during competition. Six jumps for each athlete were analysed. A point of steering was clearly identifiable, however this point had no consistent effect on the velocity profiles of the athletes. Two of the athletes maintained their velocity, and the third increased his velocity after this point was reached. Stride patterns from this point were not related to steering. It was found that most of the adjustment in stride pattern occurred in the last two strides, and this may have been responsible for the observed reduction in velocity immediately prior to takeoff. Practical solutions for altering and practising the run-up rhythm are discussed.